The Physical Fitness Level of College Students Before and After Web-Based Physical Education During the COVID-19 Pandemic - Xia, Wei; Huang, Cai-hong; Guo, Yu; Guo, Min-gang; Hu, Ming; Dai, Jian; Deng, Cheng-hu (Frontiers in Pediatrics, 2021)
Background: The COVID-19 pandemic has been an emergency worldwide. Web-based physical education is a choice for college students to keep on their study. The aim of this study was to compare the data of physical fitness of college students before and after web-based physical education. Methods: All the 2018’s and 2019’s students in Wuhan university of technology who had taken the web-based physical education class in 2020 were included in this study. The records of annually physical fitness tests of all the subjects in 2019 and 2020 which were carried out in September were reviewed, including weight, height, body mass index (BMI), vital capacity (VC), 50-meter dash, sit-and-reach, standing long jump, male-specific pull-ups and 1000-meter race, and female-specific sit-ups and 800-meter race. Results: There were 24112 male and 9690 female records of physical fitness tests included in our study. The results of 11219 male and 4651 female students who completed both physical fitness tests in 2019 and 2020 were employed for Wilcoxon signed-rank testpaired T-test. Declined performance was observed on male 50-meter dash by 0.1 second, male 1000-meter race by 14 second and female 800-meter race by 11 second. Notably, the percentage of male obesity, based on BMI, rose form 10.6% to 15.2%, 17.1% to 21.8% for male overweight; correspondingly, the percentage of male normal weight declined from 55.9% to 51.9%, 16.4% to 11.1% for male thinness. The trend of increasing BMI in male should be paid attention to. Improved results on vital capacity, sit-and-reach, standing long jump for both males and females, female 50-meter dash, female sit-ups and male pull-ups were observed in 2020. All the results of physical fitness tests were significantly different between 2019 and 2020 (P<.01) by Wilcoxon signed-rank testpaired T-test. Conclusions: The changes of physical fitness tests before and after web-based physical education suggested that the focus should be placed on improvement for running tests through appropriate alternatives, such as fast running in place and shuttle run. And the simplye, convenient and practical sport that require available equipment and little field should be considered for web-based physical education.